Shared, collaborative and on demand: the new digital economy - Smith, Aaron (Washington, DC, 2016)
"The sharing economy and on-demand services are weaving their way into the lives of (some) Americans, raising difficult issues around jobs, regulation and the potential emergence of a new digital divide. A number of new commercial online services have emerged in recent years, each promising to reshape some aspect of the way Americans go about their lives. Some of these services offer on-demand access to goods or services with the click of a mouse or swipe of a smartphone app. Others promote the commercialized sharing of products or expertise, while still others seek to connect communities of interest and solve problems using open, collaborative platforms. These services have sparked a wide-ranging cultural and political debate on issues such as how they should be regulated, their impact on the changing nature of jobs and their overall influence on users’ day-to-day lives."